Information and inclusive communication for Peruvian Amazon - Eto, Guadalupe (2009)
This arricle is about the implementation ofinformation and communication systems to improve the access to forest information, in the productive chains of rural producers of the Peruvian Amazonian rainforest ofLorew. T he author refers to her experience as a communication specialist in the multitask team of che Proyecto Focal Bosques, developed in the Instituto de Investigaciones de la Amazonía Peruana, with the support of the European Commission, one of its results was to strength the capacity of the rural communities producers, in sustainable technologies and in economical interchange, with the support of the Forest Information System Siforestal, that combined tradicional and hi-tech communication media, as radio, television, community panels, web pages and internet. The analysis of this experience includes social, in rhe approximation to the rural life of the Peruvian rainforest man, that many, even politic deciders know weakly; from development communication, that allowed the construction of sense for the design and implementation of Siforestal, by approximate to reception and feedback of promotion messages of sustainable development of rainforest, and from the experience in the university build of communicators, innovaring in non-urbanambits the sustainabílity that may give universities to derivated initiatives of developmem communication projects that contribute toa improved life quality of one of the most depressed and unattended areas of the country.